(untitled) (Palíndromo, 2013)
The artist Giuseppe Penone follows the traces left in the substances where he sculpts to reveal, in the sculpture, life forms that inhabit those materials. As formulated by Georges Didi-Huberman, making sculpture is to Penone, making a excavation. His work could be thought as a kind of archeology, in which, proceeding by the materical excavation he reveals overlooked worlds. The exercise that we propose here is to critically unfold the issues brought up by his archaeological work in order to proceed in a similar manner: follow the marks left in the material in which he sculpts - or excaves - to inquire, then, what is the nature of those worlds revealed by his excavations-sculpture.